Syphilis. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 1: early and late syphilis - Anna Wojas-Pelc; Maciej Pastuszczak; Agnieszka B. Serwin; Iwona Rudnicka; Sławomir Majewski; Rafał Czajkowski; Iwona Flisiak; Waldemar Placek; Joanna Maj; Romuald Maleszka; Lidia Rudnicka (Termedia Publishing House, 2018)
Syphilis (lues) is a systemic bacterial disease caused by Treponema pallidum subsp. pallidum , which is mainly sexually transmitted or can be acquired by an unborn foetus via the placenta. Due to its numerous symptoms, including various cutaneous and mucosal manifestations, diagnosis and treatment should be performed by dermatology and venereology experts. The incidence of syphilis has been incresing in the last years and syphilis has become a significant epidemiological problem in contemporary medicine. Contrary to a number of other infectious diseases, etiological agents of syphilis have never been cultured. Thus, diagnostic standards are based on indirect methods, such as serological tests. They are also used for monitoring treatment efficacy. Parenteral penicillin remains the gold standard in therapy of syphilis. Part 1 of recommendations discusses in detail the clinical presentation, diagnostics, and treatment of early and late syphilis, excluding central nervous system syphilis and syphilis in pregnancy.